Comparison of Anxiety Levels in MDR-TB Patients with Individual and Short-term Regimens at Dr. Soebandi Regional General Hospital, Jember, Indonesia - Widodo, Muhammad Rifqy Alvy; Astuti, Ida Srisurani Wiji; Kusumastuti, Inke; Raharjo, Angga Mardro; Supangat, Supangat; Tyaswati, Justina Evy; Zulkifli, Noor Fadzilah binti (Faculty of Medicine Universitas Airlangga, 2024)
Introduction: Multidrug-resistant tuberculosis (MDR-TB) is a form of TB that shows resistance to both isoniazid and rifampicin. Globally, the number of new MRD-TB cases has continued to rise since 2020. Indonesia is positioned among the top ten countries with the highest incidence of MDR-TB worldwide. Specifically, Jember ranked second in the number of MDR-TB cases in East Java. This study aimed to assess the comparison between the administration of individual MDR-TB regimens and short-term regimens concerning anxiety levels in MDR-TB patients at Dr. Soebandi Regional General Hospital, Jember. Methods: This was an analytical observational study with a cross-sectional design. It was conducted at Dr. Soebandi Regional General Hospital, Jember, using interviews and medical record data from August to September 2023. The sample size was 69 participants, who were obtained through consecutive sampling. Analysis was performed using the Statistical Package for the Social Sciences (SPSS) and the Chi-Square test for group comparisons. Results: This study found that 64% of subjects received individual regimens. In the individual regimen group, 80% of subjects reported anxiety. Among the short-term regimen group, 60% of subjects showed no anxiety. The significance value of this study was 0.007 in the Chi-Square test for group differences. Conclusion: There was a difference in anxiety levels between individual and short-term regimens among MDR-TB patients at Dr. Soebandi Regional General Hospital, Jember. Patients with anxiety were more common in individual regimens compared to short-term regimens.